Post Total Thyroidectomy Hypocalcemia in Toxic MNG and Effect of Post-operative Intravenous Calcium Gluconate in its Incidence - Muhammad Ahsan Mustafa; Muhammad Saeed Akhtar; Muhammad Hassan Abbas; Sajjad Ahmad Ansari; Kaleem Akhtar; Fatima Akram (Pakistan Armed Forces Medical Journal, 2026)
Objective: To see the effects of post-operative intravenous calcium gluconate infusion on post-total thyroidectomy calcium levels in toxic multinodular thyroid patients. Study Design: Randomized control trial (IRCT20240503061640N1). Place and Duration of Study: Combined Military Hospital Bahawalpur, Pakistan from Nov 2023 to Jul 2024. Methodology: Patients with toxic multinodular goiter and having normal calcium levels were included. Baseline parameters, history, and pre-operative calcium levels were measured. Patients were divided into two groups: one interventional group which was given intravenous calcium gluconate infusion, and the other control group was given intravenous normal saline infusion as a placebo. Post-operative measures like calcium level, hospital stay, severe hypocalcemia symptoms, Chvostek sign, Trousseau sign and need for calcium supplements were noted. Results: Out of seventy-two patients 36 were assigned to each group. Both group shows no significant difference between baseline parameters. The mean value of the post-operative calcium level of the interventional group was 9.472±0.582 mg/dl and the control group was 8.863±0.555 mg/dl with a statistically significant difference (p-value <0.001). The control group shows a significant number of hypocalcemia patients as compared to the interventional group with a p-value of 0.017. Conclusion: This study concluded that the post-operative use of calcium gluconate reduces the incidence of hypocalcemia in post-thyroidectomy patients with toxic multinodular goiter. Not only does it reduce severe symptoms of hypocalcemia but also reduces the post-operative need for calcium supplements and hospital stay thus ensuring better recovery.